2012
DOI: 10.1016/j.sbspro.2012.09.872
|View full text |Cite
|
Sign up to set email alerts
|

Proposals for Improvement of the Italian Roundabout Geometric Design Standard

Abstract: The paper presents a critical review of the Australasian, EU and US roundabout geometric design standards and guidelines and identifies inconsistencies of the Italian roundabout standard which deserve improvement. As a result, recommendations for improvement of the Italian standard are proposed. These recommendations are mainly based on the concepts of design flexibility and performance based design. Indeed, rigid standards which do not really take into account safety and operational consequences of the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
1
9
0
3
Order By: Relevance
“…The entry deviation angle is inversely proportional with circulating speed, which is in agreement with Daniels et al (2011). This is expected as increasing entry curvature increases entry angle and leads to a decrease in the entry speed (Montella et al 2012).…”
Section: Analysis and Model Developmentsupporting
confidence: 78%
See 1 more Smart Citation
“…The entry deviation angle is inversely proportional with circulating speed, which is in agreement with Daniels et al (2011). This is expected as increasing entry curvature increases entry angle and leads to a decrease in the entry speed (Montella et al 2012).…”
Section: Analysis and Model Developmentsupporting
confidence: 78%
“…Antov et al (2009) found that the midblock speed (speed at the middle of the road link before the roundabout) and the inscribed circle diameter (diameter of the circle formed by the outer edge of the road around the roundabout) affect the roundabout speed, and noticed that roundabout speeds are up to half of the midblock speeds. Montella et al (2012) have identified the entry path radius (the…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, roundabouts are widely used in different countries as is stated by [4] and shown in Table1. The basic features of roundabout must be generally described for its importance.…”
Section: Introductionmentioning
confidence: 99%
“…Çok şeritli dönel kavşaklarda dolaşım yolu genişliği şerit başına 3.5 metre ile 4.9 metre arasında değişmektedir. Fransa ve İtalya' da dolaşım yolu şeridi, takip edilecek şerit çizgileri olmadan tek ve geniş bir şerit şeklinde bulunmaktadır[96]. Çoğu standart ve kılavuz tarafından dönel kavşak yaklaşımlarında kullanılması tavsiye edilen ayırıcı adalar, her bir kol üzerinde, kavşağa giren ve çıkan trafiği ayırmak ve yönlendirmek üzere şekillendirilmiş alanlar olarak tanımlanmaktadır.…”
unclassified